PERTANGGUNG JAWABAN HUKUM AKIBAT WANPRESTASI DALAM PELAKSANAAN PERJANJIAN UMROH ANTARA BIRO PERJALANAN UMROH/HAJI DENGAN JAMAAH UMROH - Khairunnisa, Khairunnisa (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTAccountability is the duty of the individual/group to take responsibility for actions that harm others, if there are irregularities would be cased. As one form of accountability bureau Umrah/Hajj that provide services and guarantees against the congregation. The liability under the auspices of the law and adjusted by agreement between the two sides. Any action relating to the law already provided for in Article 45 of Law No.13 of 2008 concerning Hajj and Umrah. This study uses normative research methods, namely doctrinaire legal research or research library, which is only indicated in the written regulations that are closely connected to the library. Of primary legal materials, secondary law and non-law material processing performed deductively in drawing conclusions from a problem that is common to concrete problems. Analyzed using descriptive technique, interpretation, legal reasoning to answer the problems that exist, namely the legal liability of default in the execution of an agreement between travel agents Umrah/Hajj with Umrah pilgrims. The result showed that with the enactment of legislation regulating the conduct of Umrah/Hajj to give legal protection to pilgrims, besides that no party would be harmed. The government’s efforts in this case the Ministry of Religious Affairs has been working that all travel agency implementation of Umrah/Hajj have a business license, but the fact in the field that cannot be implemented thoroughly, as seen from the number of data register Bureau Implementation of Hajj/Umrah in the Ministry of Religion in particular Samarinda city is not equal to the number of existing Bureau.Keywords : Accountability bureau Hajj/Umrah, Wanprestasi, The tort Umrah Agreement.